FAKTOR-FAKTOR YANG MELATARBELAKANGI PEMBERIAN ASI PADA BAYI USIA 6-12 BULAN DI PUSKESMAS MOJOSARI KABUPATEN MOJOKERTO - Dyah Siwi Hety; Ika Yuni Susanti (Hospital Majapahit (JURNAL ILMIAH KESEHATAN POLITEKNIK KESEHATAN MAJAPAHIT MOJOKERTO), 2022)
Breastfeeding exclusively for 6 months has been scientifically proven to meet the nutritional needs of infants. The decline in breastfeeding rates and the increasing use of infant formula due to the factors influencing the lack of knowledge of breastfeeding mothers and inadequate conditions for working mothers. Therefore, this study aims to determine the factors underlying breastfeeding. Descriptive research design where the population of all mothers who are breastfeeding in infants aged 6-12 months as many as 40 people. saturated samples using sampling techniques or take all the members of the population is 40 people, the research conducted on September 10 2021 to 1 Pebruary, 2022 in the Mojosari Health Center Mojokerto by using questionnaires and check list. The study found that a good fraction of respondents knowledgeable about breastfeeding in infants aged 6-12 months as many as 18 respondents (42.5%), the average respondent is not working as many as 24 respondents (60%), the average respondent had get as many as 21 respondents (52.5%). Breastfeeding in infants aged 6-12 months based on research results are also influenced by the knowledge of mothers about breast feeding, maternal employment factors and factor the information obtained by the importance of breast-feeding mothers to their babies. Knowledge about breastfeeding, job and information affected mother dor breastfeeding body and therefore needs to be increased again in the provision of information and actively seek information about the mother's milk to increase motivation in breastfeeding